2022
DOI: 10.1002/suco.202100754
|View full text |Cite
|
Sign up to set email alerts
|

Slender precast voided slabs underwalking‐inducedvibration

Abstract: Disturbance/discomfort caused by vibrations, induced by pedestrian walking on slabs in residential/office buildings, is a typical design issue for lightweight slender slabs, including prestressed concrete ones. Precast slabs are typically made with pretensioned members which allow for only partial collaboration in the transverse slab direction, which becomes even less effective when they are dry-assembled without cast-in-situ topping since it relies on the arrangement of mutual mechanical connections only. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Similarly, Dal Lago et al recently performed heel-drop and walking tests on a number of concrete floors made with voided members and found that the floors had a fundamental frequency of around 8 Hz and an equivalent viscous damping ratio of just 1% in the absence of finishes, furnishing and partitions. The measured root-mean-square acceleration response due to walking was up to 0.051 m/s 2 which exceeded the recommended thresholds for human comfort in an office environment [20]. In another study, the dynamic tests performed on 26 waffle concrete floors revealed a modal damping of at least 3.4% thanks to the contribution of non-structural elements such as partition walls [21].…”
Section: Introductionmentioning
confidence: 82%
“…Similarly, Dal Lago et al recently performed heel-drop and walking tests on a number of concrete floors made with voided members and found that the floors had a fundamental frequency of around 8 Hz and an equivalent viscous damping ratio of just 1% in the absence of finishes, furnishing and partitions. The measured root-mean-square acceleration response due to walking was up to 0.051 m/s 2 which exceeded the recommended thresholds for human comfort in an office environment [20]. In another study, the dynamic tests performed on 26 waffle concrete floors revealed a modal damping of at least 3.4% thanks to the contribution of non-structural elements such as partition walls [21].…”
Section: Introductionmentioning
confidence: 82%